Closure to Local Scour at Triangular Labyrinth Side Weirs Located on an Alluvial Channel by Mustafa Tunc, Muhammet Emin Emiroglu, and Mustafa Gogus - Tunc, Mustafa; Emiroglu, Muhammet Emin; Gogus, Mustafa (Asce-Amer Soc Civil Engineers, 2023)
[Abstract Not Available]